Effectiveness Test of Bay Leaf Ethanol Extract as Antihyperuricemia Invivo - Hilda S; Rosnike Merly Panjaitan; Nurul Hidayah (Universitas Islam Negeri Sumatera Utara, Medan, 2025)
The imbalance between high production and low excretion of uric acid in the body causes hyperuricemia, which can lead to gout. This disease is the second largest after stroke in Indonesia. Conventional therapy is not free from adverse effects. The tendency of society to go back to nature and the government's